First report of four deep-sea chondrichthyans (Elasmobranchii and Holocephali) from Andaman waters, India with an updated checklist from the region - R.R. Kumar; S. Venu; K.V. Akhilesh; K.K. Bineesh; P.T. Rajan (Acta Ichthyologica et Piscatoria, 2018)
This paper confirms the new distributional records of four rare deep-water chondrichthyans viz. sharpnose sevengill shark, Heptranchias perlo (Bonnaterre, 1788); bluntnose sixgill shark, Hexanchus griseus (Bonnaterre, 1788); bramble shark, Echinorhinus brucus (Bonnaterre, 1788); and sicklefin chimaera, Neoharriotta pinnata (Schnakenbeck, 1931) from the Andaman waters in the Indian EEZ. The above-mentioned four fish species have not been reported earlier from this region. More exploratory surveys in the region are essential to understand the diversity and distribution pattern which is essential for critical management actions. An updated checklist of chondrichthyans known from Andaman and Nicobar waters of India is also presented.